Electronic Properties of Novel Mid-Infrared Materials and Devices - Di Paola, D.M. (2019)
This thesis describes the effects of the combined incorporation of nitrogen (N) and hydrogen (H) atoms in the narrow gap III-V InAs semiconductor. The plasmonic properties of the dilute nitride In(AsN) alloy are investigated before and after the post-growth incorporation of H-atoms. The hydrogenation of In(AsN) leads to a substantial increase of the electron density near the surface. The optical excitation of In(AsN):H creates a mid-infrared (MIR) surface plasmon polariton (SPP) mode detected by reflectance techniques. The plasmonic response of the highly doped In(AsN):H compound is spatially tailored and suppressed by different techniques, such as laser or electron beam annealing, as probed by Raman spectroscopy and scanning electron microscopy (SEM). This approach enables the control of the electron density of a highly doped semiconductor by changing its chemical composition on the m-scale. Furthermore, the effects of the incorporation of N in the quantum well (QW) layer of an In(AsN)/(InAl)As resonant tunnelling diode (RTD) are presented. We show that the N-incorporation leads to the creation of strongly localized zero-dimensional (0D) states in the band gap of In(AsN). These contribute to an extended and weakly temperature dependent negative differential resistance (NDR) in the current-voltage (I-V) characteristic of the diode, not observed in N-free RTDs. This behaviour is attributed to a new type of Zener tunnelling assisted by N-related 0D states, whose size is probed by magneto-tunnelling experiments. These N-related states also contribute to the tuning of the MIR electroluminescence (EL) of the RTD, which notably also shows the occurrence of up-conversion up to room temperature.